Effect of silicon on activity coefficients of Bi, Cd, Sn, and Ag in liquid Fe‐Si, and implications for differentiation and core formation. (4th April 2019) - Righter, K.; Pando, K.; Ross, D. K.; Righter, M.; Lapen, T. J.
Abstract: The depletion of volatile siderophile elements (VSE) Sn, Ag, Bi, Cd, and P in mantles of differentiated planetary bodies can be attributed to volatile‐depleted precursor materials (building blocks), fractionation during core formation, fractionation into and retention in sulfide minerals, and/or volatile loss associated with magmatism. Quantitative models to constrain the fractionation due to core formation have not been possible due to the lack of activity and partitioning data. Interaction parameters in Fe‐Si liquids have been measured at 1 GPa, 1600 °C and increase in the order Cd (~6), Ag (~10), Sn (~28), Bi (~46), and P (~58). These large and positive values contrast with smaller and negative values in Fe‐S liquids indicating that any chalcophile behavior exhibited by these elements will be erased by dissolution of a small amount of Si in the metallic liquid. A newly updated activity model is applied to Earth, Mars, and Vesta. Five elements (P, Zn, Sn, Cd, and In) in Earth's primitive upper mantle can largely be explained by metal‐silicate equilibrium at high PT conditions where the core‐forming metal is a Fe‐Ni‐S‐Si‐C metallic liquid, but two other—Ag and Bi—become overabundant during core formation and require a removal mechanism such as late sulfide segregation. All of the VSE in the mantle of Mars are consistent with core formation in a volatile element depleted body, and do not require any additional processes. Only P and Ag in Vesta's mantle are consistent with combined core formation and volatile‐depleted precursors, whereas the rest require accretion of chondritic or volatile‐bearing material after core formation. The concentrations of Zn, Ag, and Cd modeled for Vesta's core are similar to the concentration range measured in magmatic iron meteorites indicating that these volatile elements were already depleted in Vesta's precursor materials.